Beyond Bostock: Implications for LGBTQ+ theory and practice. Issue 1 (2nd January 2021) - McCandless, Sean; Elias, Nicole M.
Abstract: The recent U.S. Supreme Court ruling in Bostock v. Clayton County is a landmark piece of case law that offers fundamental rights to LGBT persons. This essay reflects on how this case arrived at the Supreme Court and its implications for theory and praxis. The overall conclusion is that cautious optimism is warranted.